The Embodiment of Consumer Knowledge - Llewellyn, Nick (Journal of Consumer Research, 2021)
AbstractAn investigation into the embodiment of consumer knowledge is presented, drawing on ethnomethodology and the allied field of conversation analysis. Analyzing video recordings of 189 service encounters at the ticket desk of an art gallery, the study explores the embodiment of consumer knowledge, how consumer knowledge is witnessable from quotidian details of customers’ embodied conduct, how they talk, move their bodies, gesture, handle objects, and cast their gaze. Consumer knowledge is shown to be socially organized, with social considerations informing what customer should know, and how customers’ faulty assertions and claims should be treated. In the way firms approach consumer knowledge, the article describes how they might create or undermine interactive value. This article breaks new ground by demonstrating that consumer knowledge is relevant for understanding the actions of consumers, not only as a result of cognitive processes but also as it is embodied.